(Fe, Cr)(OH)3 Coprecipitation in Solution and on Soil: Roles of Surface Functional Groups and Solution pH - Zhang, Suona; Cheng, Liang; Zuo, Xiaobing; Cai, Dawei; Tong, Ke; Yandi* Hu; Ni, Jinren (Environmental Science & Technology, 2023)
he simultaneous precipitation of (Fe, Cr)(OH)3 nanoparticles in solution (homogeneous) and on soil surfaces (heterogeneous), which controls Cr transport in soil and aquatic systems, was quantified for the first time in the presence of model surfaces, i.e., bare and natural organic matter (NOM)-coated SiO2 and Al2O3. Various characterization techniques were combined to explore the surface-ion-precipitate interactions and the controlling mechanisms. (Fe, Cr)(OH)3 accumulation on negatively charged SiO2 was mainly governed by electrostatic interactions between hydrolyzed ion species or homogeneous (Fe, Cr)(OH)3 and surfaces. The elevated pH through protonation of Al2O3 surface hydroxyls resulted in higher Cr/Fe ratios in both homogeneous and heterogeneous coprecipitates. Due to ignorable NOM adsorption onto SiO2, the amounts of (Fe, Cr)(OH)3 precipitates on bare/NOM-SiO2 were similar; contrarily, attributed to favored NOM adsorption onto Al2O3 and consequently carboxyl association with metal ions or (Fe, Cr)(OH)3 nanoparticles, remarkably more heterogeneous precipitates harvested on NOM-Al2O3 than bare-Al2O3. With the same solution supersaturation, the total amounts of homogeneous and heterogeneous precipitates were similar irrespective of the substrate type. With lower pH, decreased electrostatic forces between substrates and precipitates shifted (Fe, Cr)(OH)3 distribution from heterogeneous to homogeneous phases. The quantitative knowledge of (Fe, Cr)(OH)3 distribution and the controlling mechanisms can assist in better Cr sequestration in natural and engineered settings.